Lithuanian road safety solutions based on intelligent transport systems - Jarašūnienė, Aldona; Batarlienė, Nijolė (Transport, 2013)
The rapid growth of traffic intensity was predetermined by the dynamic change in the number of cars and the need for carriage. Vehicle congestion and high risk of accidents result in disappointment of many drivers and public transport users, causing psychological tension and increasing the accident rate. The accident rate is one of key indicators that help measuring processes of the transport system and its development. With the help of various road safety solutions, the modern world aims to ensure safe transportation and achieve reduction in the number of traffic accidents. Just as any other country, Lithuania is focusing on these issues as well. Reduction in the number of traffic accidents requires implementation of the national road traffic safety policy, which is one of the most important instruments that specify directions to be taken while implementing road safety solutions for roads with the highest traffic accident rate. The paper presents a methodology for calculating traffic intensity, which can be used while addressing road safety problems. The article describes the importance of Intelligent Transportation Systems (ITSs) for road safety issues and analysis of key traffic safety determinants. The core functions of ITSs are work with information and control of technologies. ITS services can make transport safer. The article examines the use of ITSs for estimation of road safety problems in Lithuania. First Published Online: 03 Apr 2013